A “Guerra do Fogo” : o uso do filme como fonte histórica para o ensino de história - Costa, Walfreds Chaves da (2024)
This dissertation aims to study the use of historical film as a historical source in the History teaching-learning process. The film Quest for Fire (1981) was used as a reference. This study aims to reflect on the use fo films in the classroom and how the educator can analyze them, being another document in addition to those already avaliable to students. The proposal is to carry out a filmic decoupage in the way that the teacher would do with students when analyzing a historical film. The study was guided by theories developed by authors who studied Cinema and History, such as Ferro (2010), Morettin (2003), Trovão (2016, 2017) and others who dedicated themselves to relating Cinema with History Teaching, such as such as Napolitano (2003), Fonseca (2009), Barros (2007), Trovão (2022), Abud (2004) and Mocellin (2009) and those who propose meaningful learning in the teaching of History such as Rüsen (2009). As a methodology, I used film analysis, decoupage the chosen film. From this, paths are outlined on how the educator can use the film in the classroom with students through problematization.